The Feasibility of Electrochemical Ammonia Synthesis in Molten LiCl–KCl Eutectics. (15th October 2019) - McPherson, Ian J.; Sudmeier, Tim; Fellowes, Joshua P.; Wilkinson, Ian; Hughes, Tim; Tsang, S. C. Edman
Abstract: Molten LiCl and related eutectic electrolytes are known to permit direct electrochemical reduction of N2 to N 3− with high efficiency. It had been proposed that this could be coupled with H2 oxidation in an electrolytic cell to produce NH3 at ambient pressure. Here, this proposal is tested in a LiCl–KCl–Li3 N cell and is found not to be the case, as the previous assumption of the direct electrochemical oxidation of N 3− to NH3 is grossly over‐simplified. We find that Li3 N added to the molten electrolyte promotes the spontaneous and simultaneous chemical disproportionation of H2 (H oxidation state 0) into H − (H oxidation state −1) and H + in the form of NH 2− /NH2 − /NH3 (H oxidation state +1) in the absence of applied current, resulting in non‐Faradaic release of NH3 . It is further observed that NH 2− and NH2 − possess their own redox chemistry. However, these spontaneous reactions allow us to propose an alternative, truly catalytic cycle. By adding LiH, rather than Li3 N, N2 can be reduced to N 3− while stoichiometric amounts of H − are oxidised to H2 . The H2 can then react spontaneously with N 3− to form NH3, regenerating H − and closing the catalytic cycle. Initial tests show a peak NH3 synthesis rate of 2.4×10 −8 mol cm −2 s −1 at a maximum current efficiency of 4.2 %. Isotopic labelling with 15 N2 confirms the resulting NH3 is from catalytic N2 reduction. Abstract : Die zentralen Herausforderungen und Möglichkeiten der Verwendung geschmolzener LiCl‐Eutektika als Medium für die direkte elektrochemische Reduktion von N2 zu Ammoniak werden identifiziert. Durch Zugabe von LiH wird N2 zu N 3− reduziert, während stöchiometrische Mengen von H − zu H2 oxidiert werden. Das H2 reagiert dann spontan mit N 3− zu NH3, H − wird regeneriert und der katalytische Zyklus geschlossen.